Delay in delivery of land, a problem to solve in PPPs: effect on users - Lama More, Antonio (2014)
This article will address release issues of real estate in transports concessions in Peru, focused in the concession Red vial N° 6 (highway concession by Public Private Partnership (PPP)).It evidence that problems of real estate transfer are originated from the draft concession Agreement, because of Peruvian government, with the purpose of led to the growth the investment through of infrastructure projects, has generate politics without evaluate studies about land transfers and their impact in execution of works. Furthermore, the currently legal framework of expropriation in Perú (that include legal framework of release of real estate) doesn’t allow at the government to manage efficiently real estate transfer.In this context, recurrent breaches of delivery of land seen in the terms originally agreed by the parties to the concession road projects, these defaults have the main effect of delay the investment opportunities set out in the Concession Contract causing delays in the benefits that users perceive about the execution of such works in terms of money and time, for example (cost of trips, accidents, vehicle operating costs and others)